Compression deformation of WC: atomistic description of hard ceramic material. (3rd November 2017) - Feng, Qing; Song, Xiaoyan; Liu, Xuemei; Liang, Shuhua; Wang, Haibin; Nie, Zuoren
Abstract: The deformation characteristics of WC, as a typical hard ceramic material, were studied on the nanoscale using atomistic simulations for both the single-crystal and polycrystalline forms under uniaxial compression. In particular, the effects of crystallographic orientation, grain boundary coordination and grain size on the origin of deformation were investigated. The deformation behavior of the single-crystal and polycrystalline WC both depend strongly on the orientation towards the loading direction. The grain boundaries play a significant role in the deformation coordination and the potential high fracture toughness of the nanocrystalline WC. In contrast to conventional knowledge of ceramics, maximum strength was obtained at a critical grain size corresponding to the turning point from a Hall–Petch to an inverse Hall–Petch relationship. For this the mechanism of the combined effect of dislocation motion within grains and the coordination of stress concentration at the grain boundaries were proposed. The present work has moved forward our understanding of plastic deformability and the possibility of achieving a high strength of nanocrystalline ceramic materials.